Contribution to the damage analysis of pipeline cracking under high pressure - Amina Ismahene, Fezazi; Belaïd, Mechab; Mokadem, Salem; Boualem, Serier (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This study aims to contribute to the prediction of pipeline damage caused by cracking in hydrocarbon-transport pipelines, subjected to high internal pressures, in response to the growing demand in industrialised countries.Methods: To achieve this objective and analyse crack propagation in terms of Stress Intensity Factor (SIF) evaluation, the Finite Element Method (FEM) was employed. The study considers the effects of the transported medium's internal pressure on the one hand, and external stresses caused by natural phenomena such as earthquakes, landslides, and others, on the other. These external stresses are represented by tensile and compressive forces. Particular attention was given to the propagation of three types of cracks: circumferential, longitudinal, and mixed-mode cracks.Results: The affected tubular structure zone is highly susceptible to mode I cracking. In contrast to the two initial types of cracking defects, an oriented crack at an angle of π/4 with respect to the pipeline's longitudinal axis develops nearly equally in modes I and II. Its growth kinetics are closely linked to its size, internal pressure, and the intensity of external forces.Tensile forces promote the opening of circumferential cracks, the closure of longitudinal cracks, and mixed-mode (I and II) propagation of oriented cracks. Conversely, compressive forces favour the closure of circumferential and oriented cracks while encouraging the opening of longitudinal cracks.Conclusion: The study reveals that, under identical loading conditions, longitudinally initiated cracks pose the greatest danger in terms of mode I crack growth. The risk of pipeline rupture is particularly high along the pipeline, and it increases significantly with higher internal pressure.
Keywords: pipeline; pressure; external forces; Finite Element Method (FEM); crack; Stress Intensity Factor